Multiplex genotype determination at a large number of gene loci. - Lin, Z (1996)
To facilitate large-scale genotype analysis, an efficient PCR-based multiplex approach has been developed. For simultaneously amplifying the target sequences at a large number of genetic loci, locus-specific primers containing 5' universal tails are used. Attaching the universal tails to the target sequences in the initial PCR steps allows replacement of all specific primers with a pair of primers identical to the universal tails and converts the multiplex amplification into "uniplex." Simultaneous amplification of 26 genetic loci with this approach is described. The multiplex amplification can be coupled with genotype determination. By incorporating a single-base mismatch between a primer and the template into the target sequences, a polymorphic site can be converted into a desirable restriction fragment length polymorphism when it is necessary. In this way, the allelic PCR products for the polymorphic loci can be discriminated by gel electrophoresis after restriction enzyme digestion. In this study, 32 loci were typed in such a multiplex way.